Multicultural jurisdictions : cultural differences and women's rights - Shachar, Ayelet, 1966- (Contemporary political theory., 2001)
"Is it possible for the state simultaneously to respect deep cultural differences and to protect the hard-won citizenship rights of vulnerable group members, in particular women? This book argues that this is not only theoretically needed, but also institutionally feasible. Shachar's fresh approach proceeds from an acknowledgment of the potentially negative effects of well-intentioned multicultural accommodation, which often forces the most vulnerable constituents of cultural groups into an impossible choice: either an allegiance to their culture, or an exercise of their rights. Rejecting prevalent normative and legal solutions to this "paradox of multicultural vulnerability," Multicultural Jurisdictions develops a powerful argument for enhancing the jurisdictional autonomy of religious and cultural minorities while at the same time providing viable legal-institutional solutions to the problem of sanctioned intra-group rights violation. This new "joint governance" approach is guided by an ambitiously innovative principle: one that strives for the reduction of injustice between minority groups and the wider society, together with the enhancement of justice within them. Shachar applies this new approach to contested social arenas, such as family law, immigration policy, and criminal justice. She shows how individuals who view themselves as simultaneously belonging to more than one membership community and subject to more than one legal authority can be empowered by their multiple affiliations. Unique in its interdisciplinary and comparative approach, this book makes a timely intervention in current multiculturalist and feminist debates by offering an in-depth exploration of practical legal-institutional solutions to vital normative dilemmas that beset diverse societies around the globe. It will interest students of political and social theory, law, religion, institutional design, as well as cultural and gender studies."--Jacket